The Validity and Reliability of the Physical Activity Questionnaires (PAQ-A) among Indonesian Adolescents during Online and Blended Learning Schooling - Atikah Rahayu; Sumaryanti Sumaryanti; Novita Intan Arovah (OVS LLC, 2022)
Research objectives. This study aimed to validate the use of the Physical Activity Questionnaire Adolescent (PAQ-A), a physical activity instrument widely used in a school setting, among Indonesian adolescents, particularly during blended learning or online schooling due to COVID-19 restrictions.   Materials and methods. This study was a cross-sectional survey of 370 Indonesian adolescents (62.2% female, mean 15±2 years) participating in online and blended learning. Participants completed the Indonesian version of the PAQ-A online. Sixty-three (17%) participants completed the same questionnaire one week later (second survey) for the test-retest reliability, from which the intraclass correlation coefficients (ICC) were calculated. Internal consistency reliability was calculated in both surveys, while confirmatory factor analysis (CFA) was analyzed from the data in the first survey. Results. The Cronbach alpha of the PAQ-A for the first and second surveys was 0.78 and 0.82, thus indicating the acceptability of internal consistency reliability. The ICC for all PAQ-A items ranged from 0.40 to 0.81, indicating fair to excellent test and retest reliability. The root means square error of approximation was 0.033 suggesting acceptable construct validity of the instrument. Conclusions. In conclusion, sufficient evidence shows the validity and reliability of the PAQ-A to justify the use of the questionnaires for measuring physical activity levels in the Indonesian adolescents in the blended learning or online schooling setting.